Welfare state politics in privatization of delivery: Linking program constituencies to left and right - Zehavi, Amos (2012)
This article asks whether alleged partisan policy convergence has eradicated differences in relation to privatization of delivery of welfare state services. The study utilizes a novel methodological approach-numerous intrastate comparisons set in a consilience research framework-to assess the extent of convergence and its underlying reasons. It explores the partisan politics of school privatization of delivery across five countries that differ in their position on the left-right continuum: England, Australia, New Zealand, Norway, and Sweden. Privatization of delivery in health care was selected as a secondary policy domain. Analysis of within-country variation in both domains indicates that there remain significant differences between left and right across all countries. The right tends to set the privatization agenda, and the left is more reluctant than the right to privatize delivery of services. This difference in approach is related to the disparate influence that public and private program constituencies have over left and right parties. - Reproduced.
Keywords: Health services; Education; Privatization; Social policy